Fear of Missing Out among Preparatory School Students (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify the fear of missing out among preparatory school students. To achieve the research objective, the researchers developed a scale of fear of missing. The scale consists of 30 items that was administered to a sample of 629 male and female students, who were selected randomly from preparatory schools in Baghdad Governorate/Rusafa II for the academic year 2023-2024. The researcher used several statistical methods to achieve the research objectives, including the one-sample T-test, the T-test for two independent samples, the Pearson correlation coefficient, the Alpha-Cronbach's formula, and the Z-test. The results showed that the research sample has a fear of missing. The research came out with several recommendations regarding educational institutions' direct guidance units, particularly in schools, to conduct seminars and to protect middle school students from the fear of missing out. Educational institutions must restore extracurricular activities, including social, cultural, and sports programs, to increase the psychological and social adjustment of students, which in turn reduces the fear of missing out.